An Experimental Model of Peripheral Vascular Disease Involving the Intravenous Injection of Oral Bacteria - Igari, Kimihiro (Ann Vasc Dis, 2016)
Objective: The purpose of this study was to observe the direct effects of oral bacteria, such as Porphyromonas gingivalis (Pg) and Treponema denticola (Td), on the peripheral vasculature. Materials and Methods: Beagles were directly injected (at various doses) with Pg or Td. Each leg vein was exposed, ligated at proximal and distal sites, and then injected with bacteria diluted with sterile saline. The collected vascular tissue was examined microscopically, and samples of the vascular tissue and blood were cultured and then subjected to the polymerase chain reaction (PCR) in order to detect the bacterial deoxyribonucleic acid (DNA). Results: No genes of the injected bacteria were detected in the Td-inoculated blood or vascular tissue samples collected 2 weeks after the injection. The Pg gene was also not detected in the blood samples collected 4 weeks after the injection although it was detected in the vascular tissue using PCR. Microscopic examinations showed that the inflammatory reactions in the perivascular tissue increased in a bacterial dose-dependent manner, as expected. Conclusion: We observed the direct effects of oral bacteria on vascular tissue. Further studies are needed to investigate the correlations between oral bacteria and systemic diseases. (This article is a translation of Jpn J Phlebol 2015; 26: 41-6.)